Safety and pharmacokinetic assessments of a novel ivermectin nasal spray formulation in a pig model - Errecalde, Jorge Oscar (2021)
Recently published data indicates that high ivermectin (IVM) concentrations suppress in vitro SARS-CoV-2 replication. Nasal IVM spray administration may contribute to attaining high drug concentrations in nasopharyngeal tissue, a primary site of virus entrance/replication. The safety and pharmacokinetic performances of a novel IVM spray formulation were assessed in a pig model. Piglets received IVM either orally (0.2 mg/kg) or by one or two nasal spray doses. The overall safety, and histopathology of the IVM-spray application site tissues, were assessed. The IVM concentration profiles measured in plasma and respiratory tract tissues after the nasal spray were compared with those achieved after the oral administration. Animals tolerated well the nasal spray formulation. No local/systemic adverse events were observed. After nasal administration, the highest IVM concentrations were measured in nasopharyngeal and lung tissues. The nasal/oral IVM concentration ratios in nasopharyngeal and lung tissues markedly increased by repeating (12 h apart) the spray application. The fast attainment of high and persistent IVM concentrations in nasopharyngeal tissue is the main advantage of the nasal over the oral route. These original results support the undertaking of future clinical trials to evaluate the safety/efficacy of the nasal IVM spray application in the prevention and/or treatment of COVID-19.